2019
DOI: 10.15414/jmbfs.2019.9.2.267-272
|View full text |Cite
|
Sign up to set email alerts
|

Lant Growth Promoting Endophytic Yeast Geotrichum Candidum (Jx 477426) From Roots of Bruguiera Cylindrica

Abstract: Dynamic mangrove ecosystems are fascinating sources of microorganisms which serve as an extraordinary habitat for the growth and development of many endophytic microorganisms. In this study, we isolated 16 endophytic fungi thriving in the mangrove species Bruguiera cylindrica, collected from Ayiramthengu in the state of Kerala, India. All the isolated endophytes were screened for their plant growth promoting activities (IAA, siderophore and HCN production, ACC deaminase activity) and enzyme production. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, all CF and DE treatments strongly enriched the populations of C. subhashii , a yeast antagonist of filamentous fungal phytopathogens ( Hilber-Bodmer et al, 2017 ), and that of G. candidum. Although the latter fungus is known to be the causal agent of decays of numerous fruits ( Palou et al, 2009 ; Talibi et al, 2012 ), it has been shown to promote growth when inoculated in plants ( Waqas et al, 2017 ) probably due to its capacity to synthesize IAA, solubilize mineral phosphate and produce VOCs that inhibit microbial phytopathogens ( Wu et al, 2012 ; Fu et al, 2016 ; George et al, 2019 ; Chen et al, 2020 ). It is worth noting that the relative abundances of most of the above microbial species were very low in the microbial populations of non-treated soils and became very high after the CF and DE treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all CF and DE treatments strongly enriched the populations of C. subhashii , a yeast antagonist of filamentous fungal phytopathogens ( Hilber-Bodmer et al, 2017 ), and that of G. candidum. Although the latter fungus is known to be the causal agent of decays of numerous fruits ( Palou et al, 2009 ; Talibi et al, 2012 ), it has been shown to promote growth when inoculated in plants ( Waqas et al, 2017 ) probably due to its capacity to synthesize IAA, solubilize mineral phosphate and produce VOCs that inhibit microbial phytopathogens ( Wu et al, 2012 ; Fu et al, 2016 ; George et al, 2019 ; Chen et al, 2020 ). It is worth noting that the relative abundances of most of the above microbial species were very low in the microbial populations of non-treated soils and became very high after the CF and DE treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the use of long-term chemical phosphate fertilizers above normal dosage has negative impacts on the environment, such as a decrease in soil quality, soil fertility, and crop yield (Jiao et al, 2012;Kaur & Reddy, 2015;Ning et al, 2017). George et al (2019) and Simarmata et al (2020), stated that endophytic microorganisms have great potential to promote growth and do not cause any pathogenic reaction to the host plant. Furthermore, phosphate-solubilizing microorganisms synthesize phosphates which are chemically and biologically undissolved.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi are microorganisms with higher phosphate solubility compared to other microorganisms (Klaic et al, 2017;Mehta et al, 2019). George et al (2019) reported that rhizome endophytic fungi produce useful active compounds for plant growth and development, such as dissolving phosphate and releasing IAA phytohormones. However, the potential of rhizome endophytic fungi in nutgrass as phosphate solvents and IAA producers has never been analyzed and published.…”
Section: Introductionmentioning
confidence: 99%